Dietary autochthonous Cetobacterium somerae CSHT supplementation enhances heat tolerance in hybrid sturgeon - Zhichao Chen; Yinshan Bai; Yuanqiong Wei; Wenhua Wu; Linmiao Li; Haoting Mai; Yepin Yu; Jinping Chen; Xiujuan Zhang (Aquaculture, 2027)

Synergistic role of microbial osmoregulation and electron transfer on enhancing high-salinity battery discharge wastewater treatment under electrochemical stimulation - Yongsen Shi; Zhinan Zheng; Yanyan Jia; Lan Tang; Haoting Quan; Kewen Li; Tianwei Hao; Lianpeng Sun; Hui Lu (Water Research, 2026)

Corrigendum to “Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy” [Chem. Eng. J. 495 (2024) 153371] - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

CFD-DEM investigation on continuous invasion behaviors of particles and evolution of pore clogging in porous media - Haoting Li; Yuting Zhao; Jipeng Li; Haoyang Yin; Cen Song; Min Hao (Computers and Geotechnics, 2026)

PFAS in bottled water from China: High prevalence of ultrashort-chain compounds, health risks, and global insights - Haoting Quan; Fahui Ji; Zhen Zhong; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Supramolecular self-assembly for probiotic delivery in food system: responsive strategies, multifunctional carriers, future perspectives - Li Song; Haoting Xu; Chaofan Chen; Yubin Zhang; Zihao Zhang; Xiangfeng Chen; Shunxun Liu; Hang Xiao; Qing Gu; Ping Li (Trends in Food Science & Technology, 2025)

Enhanced performance of algal-bacterial granular sludge in treating wastewater under PFOA stress: Synergistic effects and mechanisms - Fahui Ji; Xiaojing Yang; Haoting Quan; Jinxia Liu; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Bioinspired dual-network CNT/PBO composite films with superior strength-ductility and thermal conductivity for flexible electronics thermal management - Guang Xiao; Kai Zhang; Hao Li; Haoting Niu; Yagang Yao (Chemical Engineering Journal, 2025)

Coexposure to ambient air pollution and temperature and its associations with birth outcomes in women undergoing assisted reproductive technology in Fujian, China: A retrospective cohort study - Dongdong Jiang; Xuefen Cai; Hua Fang; Yuehong Li; Ziqi Zhang; Haoting Chen; Zixin Zheng; Wenxiang Wang; Yan Sun (Journal of Hazardous Materials, 2025)

Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2024)

Antibody-based near-infrared fluorogenic probes for wash-free imaging of cell-surface proteins - Haoting Wang; Jiaqi Yan; Wenchao Wang; Endong Chen; Di Chen; Su Zeng; Quan Li; Linghui Qian (Analytica Chimica Acta, 2024)

Novel Janus polyurethane sponges with asymmetric wettability enabling all-weather stable and efficient remediation of crude oil spills in harsh environments - Wenqing Han; Yehai Yan; Huifang Wang; Peng Li; Haoting Lin; Jinzhong Li; Jian Cui; Guangfa Zhang (Journal of Water Process Engineering, 2024)

Association of ambient air pollution and pregnancy rate among women undergoing assisted reproduction technology in Fujian, China: A retrospective cohort study - Hua Fang; Dongdong Jiang; Ye He; Siyi Wu; Yuehong Li; Ziqi Zhang; Haoting Chen; Zixin Zheng; Yan Sun; Wenxiang Wang (Science of The Total Environment, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Identification of novel genes in Behcet’s disease using integrated bioinformatic analysis - Si Chen; Haolong Li; Haoting Zhan; Xiaoli Zeng; Hui Yuan; Yongzhe Li (Immunologic Research, 2022)
Behcet’s disease (BD) is a chronic vascular inflammatory disease. However, the etiology and molecular mechanisms underlying BD development have not been thoroughly understood. Gene expression data for BD were obtained from the Gene Expression Omnibus database. We used robust rank aggregation (RRA) to identify differentially expressed genes (DEGs) between patients with BD and healthy controls. Gene ontology functional enrichment was used to investigate the potential functions of the DEGs. Protein–protein interaction (PPI) network analysis was performed to identify the hub genes. Receiver operating characteristic analyses were performed to investigate the value of hub genes in the diagnosis of BD. GSE17114 and GSE61399 datasets were included, comprising 32 patients with BD and 26 controls. The RRA integrated analysis identified 44 significant DEGs among the GSE17114 and GSE61399 CD4 + T lymphocytes. Functional enrichment analysis revealed that protein tyrosine/threonine phosphatase activity and immunoglobulin binding were enriched in BD. PPI analysis identified FCGR3B as a hub gene in the CD4 + T lymphocytes of BD patients. Our bioinformatic analysis identified new genetic features, which will enable further understanding of the pathogenesis of BD.

An iterative damped least-squares algorithm for simultaneously monitoring the development of hemorrhagic and secondary ischemic lesions in brain injuries - Xuechao Liu; Haoting Li; Hang Ma; Canhua Xu; Bin Yang; Meng Dai; Xiuzhen Dong; Feng Fu (Medical & Biological Engineering & Computing, 2019)